Діяльність органів місцевого само врядування південнобессарабських міст щодо запобігання зростанню цін на товари першої необхідності у часи Першої світової війни - Дроздов, В. (Краєзнавство, 2020)
Досліджено діяльність муніципальних органів влади південнобессарабських міст щодо запобігання
зростанню дорожнечі у 1914-1915 рр. На основі аналізу протоколів засідань органів міського самоврядування та інших архівних документів визначено причини дорожнечі, її вплив на рівень життя міського
населення Південної Бессарабії й охарактеризовано основні заходи органів місцевого самоврядування,
спрямовані на утримання цін на товари першої необхідності та боротьбу зі спекуляцією. З’ясовано,
що умови воєнного часу, поглиблення продовольчої кризи й несприятлива фінансова ситуація завадили
спробам місцевого самоврядування південнобессарабських міст зупинити зростання цін. Автором визначено специфічні чинники, пов’язані з прикордонним розташуванням регіону, що негативно вплинули на продовольчу ситуацію в містах і сприяли дорожнечі. Based on the analysis of a wide range of archival sources from the funds of the National Archives of the
Republic of Moldova and Municipal Institution “Ismail Archive” the reasons for growth of prices in the Southern
Bessarabian cities (Akerman, Izmail, Reni, Kilia and Bolgrad) in 1914–1915 were revealed, the taxation
of essential goods as the main method of the fight against high prices was described, other local self-governments’
measures on the price normalization and the counteracting speculation were characterized and the results
of their activities during the initial period of the First World War were determined.
It is established that during 1914–1915 the tasks of the population’s food supply and the fight against high
prices were entrusted by the tsarist government to the local authorities and local self-government. With the
growing food crisis, the issue of the price regulation for essential goods has been increasingly discussed at
local council meetings. Special attention was paid to the analysis of minutes of the municipal councils meetings,
which had considered ways of the price normalization and the counteracting speculation.
It is revealed that wartime conditions, intensification of the food crisis and unfavorable financial situation
have hampered attempts by local self-governments in the Southern Bessarabian cities to halt price rises. The
author identified specific factors related to the border location of the region that adversely affected by the food
situation and contributed to the high prices in the cities.